2017
DOI: 10.1111/adb.12580
|View full text |Cite
|
Sign up to set email alerts
|

Increased plasma oleoylethanolamide and palmitoleoylethanolamide levels correlate with inflammatory changes in alcohol binge drinkers: the case of HMGB1 in women

Abstract: Alcohol binge drinking is a heavy pattern of alcohol consumption increasingly used by young people. In a previous study, we reported that young drinkers with a 2-year history of binge alcohol consumption had an overactivation of the innate immune system and peripheral inflammation when compared with controls. In the present study, we measured several biolipids that are fatty acid derivatives belonging to the acylethanolamide or 2-acylglycerol families in the plasma of the same subjects (n = 42; 20 men and 22 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 13 publications
1
16
0
Order By: Relevance
“…Increased OEA release in the small intestine was observed in response to alcohol in vivo (Bilbao et al ., ) and to inflammation in vitro (Karwad et al ., ), suggesting a local role of OEA in regulating alcohol responses and intestinal permeability respectively. The idea that inflammation may trigger the release of OEA has been also proposed in our previous studies, in which we observed exacerbated inflammatory responses and increased plasma OEA levels in human alcohol binge drinkers (Orio et al ., ; Antón et al, ). Alcohol also induced neuroinflammation and OEA release in the frontal cortex of laboratory animals (Bilbao et al ., ; Antón et al ., ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Increased OEA release in the small intestine was observed in response to alcohol in vivo (Bilbao et al ., ) and to inflammation in vitro (Karwad et al ., ), suggesting a local role of OEA in regulating alcohol responses and intestinal permeability respectively. The idea that inflammation may trigger the release of OEA has been also proposed in our previous studies, in which we observed exacerbated inflammatory responses and increased plasma OEA levels in human alcohol binge drinkers (Orio et al ., ; Antón et al, ). Alcohol also induced neuroinflammation and OEA release in the frontal cortex of laboratory animals (Bilbao et al ., ; Antón et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…In previous studies, we demonstrated that pharmacological pretreatment with oleoylethanolamide (OEA), a lipid mediator part of the acylethanolamide family, during the alcohol binge episodes has potent anti‐inflammatory, antioxidant and neuroprotective properties against the effects of alcohol and partially reduced alcohol binge‐induced increases in plasma LPS levels in rats (Antón et al ., ). In humans, we observed that regular alcohol binge drinkers show elevated plasma levels of LPS and inflammatory markers (Orio et al ., ) and increased plasma levels of OEA and similar biolipids (Antón et al ., ), suggesting a homeostatic role for this biolipid in regulating alcohol responses (Bilbao et al ., ). The main hypothesis that we tested in this study was whether the anti‐inflammatory actions of OEA may have a local action in the gut, regulating inflammation and barrier permeability.…”
Section: Introductionmentioning
confidence: 99%
“…The gene and protein expression of HMGB1 were increased in hippocampal-entorhinal cortical cell treated with ethanol, an effect associated with increased gene expression of TNF-α and IL-1β [47]. In clinical studies, elevation of HMGB1 levels has been observed in alcohol binge female drinkers [48]. Additionally, postmortem human alcoholic hippocampus showed an increase in the HMGB1expression [49].…”
Section: Introductionmentioning
confidence: 94%
“…OEA, a high affinity endogenous ligand of PPAR-α (28), binds to PPAR-α receptors, and increases the expression level of anti-inflammatory cytokine such as IL-10. In addition, it attenuates the inflammatory responses and decreases the expression of TLR4, and interfering with the ERK1/2/AP-1/STAT3 signaling cascade (29)(30)(31). In a recent clinical trial, OEA supplementation could decrease inflammation in obese patients via reducing serum concentrations of inflammatory markers including IL-6 and TNF-α (32).…”
Section: Oleoylethanolamide and Sars-cov-2 Infectionmentioning
confidence: 99%